A MODEL FOR PREDICTING CONCRETE DECK DAMAGE RATE OF STEEL TRUSS BRIDGE IN INDONESIA - Sulistyono, Djoko; Alisjahbana, Sofia W.; Ma’some, Dadang (CENTRAL ASIA AND THE CAUCASUS, 2022)
Bridge maintenance is structural repair work so that it is always in good condition to serve goods and services transportation traffic. There are three levels of maintenance: routine, periodic, and rehabilitation. Effective treatment depends on the scale of the damage, starting from 0 (Excellent), 1, 2, 3, 4, and 5 (Very Bad). So it is crucial to create a reference model for changes from 0 - 5. Floor elements, as the primary function of bridge services, are damaged faster, so the type of maintenance should be precise.Research shows that the age of destruction varies from 2 to 45 years. The researchers make the model for 220 bridges, with construction age, traffic load, concrete quality, and others as independent variables.SPSS processing produces the expected model curve. Multiple linear regression analysis points non-linear curve consisting of the dominant factors causing the damage, while the ordinal logistic regression makes an integer scale. The model demonstrates a 5-scale collapse, which occurred around 54 years, and others. So, this prediction is the right program for handling with optimum financing.